2004
DOI: 10.1136/adc.2003.032599
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Alder Hey Triage Pain Score

Abstract: Aims: To describe the validation and reliability of a new pain tool (the Alder Hey Triage Pain Score, AHTPS) for children at triage in the accident and emergency (A&E) setting. Methods: A new behavioural observational pain tool was developed because of dissatisfaction with available tools and a lack of confidence in self-assessment scores at triage. The study was conducted in a large paediatric A&E department; 575 children (aged 0-16 years) were included. Inter-rater reliability and various aspects of validity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 11 publications
3
38
0
3
Order By: Relevance
“…Studies that evaluate other oral NSAIDs, including naproxen, in the ED are needed. Based on the results of the systematic review, we can conclude that, for the initial treatment of mild acute pain in children in the ED, it is probably better to administer ibuprofen first, Studied age [16] Score Treatment threshold [22] Psychometric properties a [21] Evidence-based assessment b [142] AHTPS [143] Observational …”
Section: Oral Paracetamol or Non-steroidalmentioning
confidence: 99%
“…Studies that evaluate other oral NSAIDs, including naproxen, in the ED are needed. Based on the results of the systematic review, we can conclude that, for the initial treatment of mild acute pain in children in the ED, it is probably better to administer ibuprofen first, Studied age [16] Score Treatment threshold [22] Psychometric properties a [21] Evidence-based assessment b [142] AHTPS [143] Observational …”
Section: Oral Paracetamol or Non-steroidalmentioning
confidence: 99%
“…17 Both of these scales, to the extent that they were validated in these specific contexts, are more appropriate when used exclusively in those situations.…”
Section: Contexts Of Pain Assessmentmentioning
confidence: 99%
“…11 Nevertheless, in the course of this literature review it was found that ordinal scales are also used by trained observers or by the medical and nursing teams to assess child pain. In these cases the following instruments were used: the Objective Pain Scale (OPS), 8 the Faces, Leg, Activity, Cry and Consolability scale (FLACC), 8,[13][14][15] the Children's Hospital of Eastern Ontario Pain Scale (CHEOPS), 8 the Pediatric Pain Profile (PPP), 16 the Alder Hey Triage Pain Score (AHTPS), 17 the Child Facial Coding System (CFCS) 18 and the Non-Communicating Children's Pain Checklist-Revised (NCCPC-R). 19 …”
Section: Measurement Scales Of the Instruments Analyzedmentioning
confidence: 99%
“…Six studies were located that evaluated different pain measurement tools in the pediatric ED (Bulloch & Tenenbein, 2002;Crellin, Sullivan, Babl, O'Sullivan, & Hutchinson, 2007;Garra et al, 2009;Schultz et al, 2002;Stewart, Lancaster, Lawson, acute pain assessment associated with chief complaint (Bulloch & Tenenbein, 2002;Garra et al, 2009;Stewart et al, 2004), one study evaluated the psychometric properties of the modified version of the pre-verbal, early verbal, pediatric pain scale (M-PEPPS) via secondary analysis from data collected on pediatric patients 12 months through 84 months however data on the nature of pain whether procedural or as a chief complaint was not identified (Strout and Baumann, 2011). Behavioral Distress (OSBD).…”
Section: Reliability Of Pain Instruments In the Edmentioning
confidence: 99%